ABS braking on rough terrain. (December 2018) - van der Merwe, Nico A.; Els, P. Schalk; Žuraulis, Vidas
Highlights: Identifies causes of performance deterioration due to rough terrain. Effects of fluctuations in the angular wheel speeds. Effects of variations in vertical loading conditions. Experimental and simulation results. Good correlation between measured and simulated tyre force using FTire. Abstract: The performance of Anti-lock Brake Systems (ABS) for vehicles deteriorate on rough terrains, due to fluctuations in the angular wheel speeds and in the vertical loading conditions of the tyre caused by the terrain inputs. In this paper, ABS braking performance on non-deformable rough terrain is investigated by performing experiments and simulations using a testing trailer and a validated multi-body dynamics model. The trailer was constructed using a Land Rover Defender chassis and installed with standard Land Rover braking components including an ABS modulator. It was found in the ABS tests performed, while using a standard Bosch ABS algorithm, that the ABS algorithm failed to perform optimally due to oscillations and irregularities that were present in the measurement of angular wheel speeds. Good correlation is found between the tyre forces measured and the forces simulated using an FTire model in MSC ADAMS software. A powerful platform was created for future off-road ABS investigation and development using both experiments and a simulation platform.